The Cat in the Hat - Dr Seuss (HarperCollins Publishers Ltd, 2003)
Cat fanciers rejoice! Available for the first time is a picture book-size, jacketed edition of The Cat in the Hat by Dr. Seuss--the classic, deliciously anarchic story of a giant cat in a hat whose unexpected arrival turns a dull, rainy day into a madcap adventure. Although written for beginning readers, The Cat in the Hat makes an ideal read-aloud for children of all ages. Highly collectible, it's a purr-fect gift for Seuss fans of all ages!
Keywords: Juvenile literature-Cat in the Hat (Fictitious character)-Animals-Cats-Fiction